Mingjing granule inhibits the subretinal fibrovascular membrane of two-stage laser-induced neovascular age-related macular degeneration in rats - Li, Xiaoyu; Li, Jiaxian; Zeng, Weixin; Wang, Baoli; Du, Maobo; Liang, Lina; Gao, Yun (Frontiers in Pharmacology, 2024)
Objective: To investigate the protective effect of Mingjing Granules (MG) in a fibrovascular membrane rat model of neovascular age-related macular degeneration(nAMD), and explore the underlying mechanism.: nAMD fibrovascular membrane model was established by two-stage laser photocoagulation. BN rats were randomly divided into four groups: model group was gavaged with distilled water, anti-VEGF group was given an intravitreous injection of ranibizumab, MG+anti-VEGF group was gavaged with MG combined with intravitreous injection of ranibizumab, and normal group not modeled only fed conventionally. Lesions were evaluated by color fundus photographs, optical coherence tomography, fundus fluorescein angiography, and RPE-choroid-sclera flat mount. The changes in retinal structure were observed by histopathology. The expression of inflammatory cell markers F4/80, Iba-1, and GFAP, the fibrosis related factors Collagen-1, Fibronectin, α-SMA, and TGF-β, the complement system related factors C3a and C3aR in retina were detected by immunofluorescence or qRT-PCR.Results: Current study revealed that MG+anti-VEGF administration more significantly reduced the thickness of fibrovascular lesions, suppressed vascular leakage (exudation area and mean density value), inhibited the area of fibrovascular lesions, and restrained the formation of fibrovascular membrane than anti-VEGF agent alone in the two stage laser-induced rat model. The fluorescence intensities of F4/80, Iba-1, Collagen-1, Fibronectin, TGF-β, and C3aR showed more significant inhibition in MG+anti-VEGF treated rats than anti-VEGF agent alone. The mRNA expression levels of F4/80, Iba-1, GFAP, Collagen 1, Fibronectin, α-SMA, TGF-β, and C3a showed lower levels in rats treated with MG+anti-VEGF than anti-VEGF agent alone.Combining MG with anti-VEGF treatment inhibit the growth of fibrovascular membrane more effectively than using anti-VEGF treatment alone. The mechanism underlying this effect may involve limiting inflammatory cell aggregation, controlling complement system activation, and decreasing the expression of the fibrotic protein.